Identifying Malicious Software Using Deep Residual Long-Short Term Memory - Aziz Alotaibi (IEEE Access, 2019)
The use of smartphone applications based on the Android OS platform is rapidly growing among smartphone users. However, malicious apps for Android are being developed to perform attacks, such as destroying operating systems, stealing confidential data, gathering personal information, and hijacking or encrypting sensitive data. Several malware detection systems based on machine learning have been developed and deployed to extract a variety of features to prevent such attacks. However, new efficient detection methods are needed to extract complex features and hidden structures from malicious apps to detect malware. This paper proposes a novel framework, namely, MalResLSTM, based on deep residual long short-term memory to identify and classify malware variants. The framework imposes a set of constraints on the deep learning architecture to capture dependencies between the extracted features from the Android package kit (APK) file. These feature sets are mapped to a vector space to process the input sequence using a sequence model based on the residual LSTM network. To evaluate the performance of the proposed framework, several experiments are conducted on the Drebin dataset, which contains 129,013 applications. The results demonstrate that MalResLSTM can achieve a 99.32% detection accuracy and outperforms previous algorithms. An extensive experimental analysis was conducted, which included machine-learning-based algorithms and a variety of deep learning-based algorithms, to evaluate the efficiency and robustness of our proposed framework.